2010
DOI: 10.1039/c0cc03528a
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth– and lead–texaphyrin complexes: towards potential α-core emitters for radiotherapy

Abstract: Lead(II)–texaphyrins and the first discrete binuclear μ–oxo bismuth(III)–texaphyrin are reported. The latter was characterized via single crystal X-ray diffraction analysis. Cell proliferation assays using the A2780 ovarian cancer cell line were used to determine the cytotoxicity of the complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…However, it has been suggested that the significant radiosensitization effect of Bi 2 S 3 NPs could be successfully realized through their inhibition effect on tumor growth in a tumor-bearing mice model, where intrinsic potential biological toxicity of sulfur element could not be ignored. 29 Furthermore, as we have known, the lower cost of bismuth element and higher radiation dose enhancement 30,31 compared to gold element could make the BiNP a better candidate for further commercial use. Thus, it is suggested that Bi 2 O 3 NP can be used as an ideal alternative to evaluate the therapeutic effect of nanomedicine-based radiosensitizers in the interstitial radiotherapy research.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that the significant radiosensitization effect of Bi 2 S 3 NPs could be successfully realized through their inhibition effect on tumor growth in a tumor-bearing mice model, where intrinsic potential biological toxicity of sulfur element could not be ignored. 29 Furthermore, as we have known, the lower cost of bismuth element and higher radiation dose enhancement 30,31 compared to gold element could make the BiNP a better candidate for further commercial use. Thus, it is suggested that Bi 2 O 3 NP can be used as an ideal alternative to evaluate the therapeutic effect of nanomedicine-based radiosensitizers in the interstitial radiotherapy research.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mixture was washed by hot Макрогетероциклы / Macroheterocycles 2016 9(2) 206-210 water from phenol, and then was extracted by hexane in a Soxhlet apparatus. The product was purified by column chromatography on silica gel, eluting impurities by CH tetranitrilo-33H,34H-1,12,17,28-tetrathiodibenzo[c,q]- (1,6,17,22)-tetraazacyclodotriacontene (9) …”
Section: Bis(5-amino-134-thiadiazol-2-yl)ethane (5)mentioning
confidence: 99%
“…Both modification of peripheral fragments of molecules and variation of the size of the coordination cavity of macrocyclic compounds allow for the development of therapeutic agents for photodynamic cancer therapy and viral disease, [1,2] as well as materials with unique optical, magnetic, semiconductor properties. [3,4] Macroheterocyclic compounds (Mc) with expanded coordination cavities comprised of 6 smaller heterocyclic moieties that are linked to each other via aza-bridges are fundamentally interesting.…”
Section: Introductionmentioning
confidence: 99%
“…39 Specifically, spectroscopic and mass spectrometric evidence was put forward to support the formation of the first lead(II) texaphyrin complexes 33 and 35 (cf. Figure 5).…”
Section: Bismuth and Lead Coordinated Texaphyrinsmentioning
confidence: 99%
“…Similar methods were used to confirm the formation of the first discrete binuclear μ -oxo bismuth(III) macrocyclic complex 34 , a system that was further characterized via a single crystal X-ray diffraction analysis. 39 …”
Section: Bismuth and Lead Coordinated Texaphyrinsmentioning
confidence: 99%